Dietary administration of vitamin C and Lactobacillus rhamnosus in combination enhanced the growth and innate immune response of the rainbow trout, Oncorhynchus mykiss - A. Tookmehchi email ; H. Shamsi; S. Meshkini; R. Delshad; A. Ghasemi Moghanjoei (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2012)
The effects of dietary vitamin C and Lactobacillus rhamnosus on immunity and growth performance were investigated in Oncorhynchus mykiss. For this purpose, 480 rainbow trout (68Â±5g) were obtained from a local farm and acclimated to laboratory conditions for 10 days and then divided into four groups in three replicates. During 30 days, juvenile rainbow trout were fed diets supplemented with vitamin C (1g/kg) and L. rhamnosus (at 5 Ã 107 CFU/g) or a control diet. Biometry was done at day -30 and blood samples were taken by caudal vein after fish anesthesia with clove powder at day 0, 15, 30 and 45. Serum lysozyme activity, alternative complement activity and total plasma immunoglobulin level were assayed as innate immune response of rainbow trout. Results showed fish fed with vitamin c and L. rhamnosus (group 3) statistically could improve fish growth performance. Also lysozyme activity and alternative complement activity of serum significantly were higher in group three than other groups, but total plasma level of immunoglobulin only was higher than all groups at day 30. In conclusion dietary administration of vitamin C and L. rhamnosus in rainbow trout diet could enhance the growth and innate immune response, but these properties need further studies on the field applications.